JEJAK PERKEMBANGAN TAREKAT SYADZILIYAH DI NUSANTARA: STUDI HISTORIS DAN SOSIOLOGIS - Firman Firman; Hafsa Hafsa; Baiq Madinatul Munawwarah; Fitrotul Muzayanah (Yayasan Haiah Nusratul Islam, 2025)
This study explores the historical and sociological trajectory of the Syadziliyah Sufi order in the Indonesian archipelago. Although less prominent than other major Sufi orders such as Qadiriyah or Naqshabandiyah, the Syadziliyah order has played a vital role in shaping the spiritual and social dimensions of Muslim communities in the region. The study applies a qualitative-descriptive method based on literature analysis to examine how the order entered the Nusantara through trade, pilgrimage, and scholarly exchange, as well as how its teachings have been adapted to diverse local cultures. Emphasizing spiritual balance, social engagement, and moderation, the syadziliyah order continues to be relevant in the modern era as a response to spiritual crises and socio-moral challenges. The findings show that its values contribute significantly to ethical development, community solidarity, and the revitalization of Islamic spirituality within the pluralistic society of Indonesia.